Cam Jansen and the mystery of the gold coins - Adler, David A.; Natti, Susanna (New York, NY Scholastic Inc., 1991)
While using her photographic memory to find her missing science fair project, Cam accidentally locates two valuable gold coins.
"A young Puffin."--Cover.
Keywords: Mystery fiction